Analisis Bahaya Abrasi di Wilayah Kabupaten Banggai Kepulauan - Wisyanto Wisyanto (Jurnal ALAMI : Jurnal Teknologi Reduksi Risiko Bencana, 2019)
The threat of abrasion even though comes as a slow onset process, but it is certainly and can disrupt the interests of the community. One of the areas that threaten by abrasion is Banggai Kepulauan Regency. To find out how big the threat of abrasion and it’s alternative handling, An abrasion hazard analysis has been carried out based on the calculation of 3 main parameters obtained from secondary data and some of them are detailed by field observations, namely wave height parameters and routinity level, coastal rock / sediment composition, and coastal slope . The results showed that the total coastal length which has a high hazard level is 250.87 km and the Liang sub-district is a district that has the longest high level of abrasion threat, which is 41.11 km long. The alternative measures for abrasion protection, in addition to the physical construction of abrasion-retaining structures as found in the field, is through the protection of green belts and the prohibition of the establishment of houses on abrasive coastal areas.